Data analysis: Comparison between the different methodological perspectives of the Grounded Theory - dos Santos J.L.G. (2018)
© 2018, Escola de Enfermagem de Universidade de Sao Paulo.Grounded Theory (GT) has undergone many transformations since its proposition as a research method in the 1960s. As a result of these changes, three different GT approaches have been outlined: classic, straussian and constructivist ground theory, each with its peculiarities, but mainly concerning data analysis. Thus, this study aimed to describe and compare the data analysis process adopted by the different methodological perspectives of GT. The text is organized into two topics. Firstly, we present the common and differentiating characteristics of the three methodological perspectives of GT. In sequence, the data analysis system adopted in each of the GT methodological perspectives is described and exemplified, varying between two and three stages, and may or may not include the use of the paradigmatic model. Thus, this study provides support for understanding the different data analysis systems adopted in GT, which may contribute to the rigor and scientific quality of nursing research adopting this method.